Respuesta :
4a + 2c = 70 ; a = 14 ; c = 7 ; 4(14) + 2(7) = 70 ; 56 + 14 = 70 ; 70 = 70
8a + 12c = 196 ; 8(14) + 12 (7) = 196 ; 112 + 84 = 196 ; 196 = 196
Get the value of a:
4a + 2c = 70
4a = 70 - 2c
4a/4 = (70 - 2c) / 4
a = (70 - 2c) / 4
Substitute the value of a:
8a + 12 c = 196
8 ((70 - 2c)/4) + 12c = 196
(8*70)/4 - (8*2c)/4) + 12c = 196
(560 / 4) - (16c / 4) + 12c = 196
140 - 4c + 12c = 196
-4c + 12c = 196 - 140
8c = 56
8c / 8 = 56 / 8
c = 7
a = (70 - 2c) / 4
a = ((70 - 2(7))/4
a = (70 - 14)/4
a = 56 / 4
a = 14
8a + 12c = 196 ; 8(14) + 12 (7) = 196 ; 112 + 84 = 196 ; 196 = 196
Get the value of a:
4a + 2c = 70
4a = 70 - 2c
4a/4 = (70 - 2c) / 4
a = (70 - 2c) / 4
Substitute the value of a:
8a + 12 c = 196
8 ((70 - 2c)/4) + 12c = 196
(8*70)/4 - (8*2c)/4) + 12c = 196
(560 / 4) - (16c / 4) + 12c = 196
140 - 4c + 12c = 196
-4c + 12c = 196 - 140
8c = 56
8c / 8 = 56 / 8
c = 7
a = (70 - 2c) / 4
a = ((70 - 2(7))/4
a = (70 - 14)/4
a = 56 / 4
a = 14
♥ First lets find the value of a
Steps we can use:
[tex]4a + 2c = 70[/tex]
[tex]4a = 70 - 2c[/tex]
[tex] \frac{4a}{4} = \frac{(70 - 2c)}{4} [/tex]
[tex]a = \frac{(70 - 2c)}{4} [/tex]
♥Now we are going to substitute for the value of a...
[tex]8a + 12 c = 196[/tex]
[tex]8 ((70 - 2c)/4) + 12c = 196[/tex]
[tex](8*70)/4 - (8*2c)/4) + 12c = 196[/tex]
[tex](560 / 4) - (16c / 4) + 12c = 196[/tex]
[tex]140 - 4c + 12c = 196[/tex]
[tex]-4c + 12c = 196 - 140[/tex]
[tex]8c = 56[/tex]
[tex]8c / 8 = 56 / 8[/tex]
[tex]c = 7[/tex]
Now moving onto A:
[tex](70 - 2c) / 4[/tex]
[tex]a = ((70 - 2(7))/4[/tex]
[tex]a = (70 - 14)/4[/tex]
[tex]a = 56 / 4[/tex]
[tex]a = 14[/tex]
Thus, if you follow these rules, you can solve:
c=7 a=14
Steps we can use:
[tex]4a + 2c = 70[/tex]
[tex]4a = 70 - 2c[/tex]
[tex] \frac{4a}{4} = \frac{(70 - 2c)}{4} [/tex]
[tex]a = \frac{(70 - 2c)}{4} [/tex]
♥Now we are going to substitute for the value of a...
[tex]8a + 12 c = 196[/tex]
[tex]8 ((70 - 2c)/4) + 12c = 196[/tex]
[tex](8*70)/4 - (8*2c)/4) + 12c = 196[/tex]
[tex](560 / 4) - (16c / 4) + 12c = 196[/tex]
[tex]140 - 4c + 12c = 196[/tex]
[tex]-4c + 12c = 196 - 140[/tex]
[tex]8c = 56[/tex]
[tex]8c / 8 = 56 / 8[/tex]
[tex]c = 7[/tex]
Now moving onto A:
[tex](70 - 2c) / 4[/tex]
[tex]a = ((70 - 2(7))/4[/tex]
[tex]a = (70 - 14)/4[/tex]
[tex]a = 56 / 4[/tex]
[tex]a = 14[/tex]
Thus, if you follow these rules, you can solve:
c=7 a=14